Association between inflammatory biomarkers and 30-day mortality in patients with acute myocardial infarction complicated by cardiogenic shock. (2nd May 2022) - Bo Kunkel, J; Josiassen, J; Helgestad, O K; Schmidt, H; Holmvang, L; Okkels Jensen, L; Berg Ravn, H; Eifer Moeller, J; Hassager, C
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Hjertecentrets Forskningsudvalg, Rigshospitalet Background: Cardiogenic shock often induces an inflammatory response, but the prognostic importance of this is not well studied. Purpose: The present study investigates whether the inflammatory response as reflected in routine blood samples taken during admission is associated with 30-day mortality in patients with cardiogenic shock due to acute myocardial infarction (AMICS). We assessed patients surviving 2 days, since a full CRP-response may take more than 48 hours to develop. Methods: Consecutive patients (N=1716) with a validated diagnosis of AMICS admitted to one of two tertiary heart centres covering a base population of approximately 4 million in the period from 2010 to 2017 were included. The median values of total leucocyte count (WBC) and C-reactive protein (CRP) corresponded well to optimum thresholds found using ROC analysis and were used as cut-off for stratification. Results: A total of 1114 (1122) of the 1716 patients were alive and had WBC (CRP) measured at day 3. Median WBC was 12.6 x 109/L. Median CRP was 146 mg/L. Patients with an elevated leucocyte response were significantly older (66 vs 64 yrs, P<.001), had a higher prevalence of diabetes mellitus (18% vs 13%) and were admitted with lower left ventricular ejection fraction (LVEF) (P<.001). Less had suffered out-of-hospital cardiac arrest (44% vs 58%, P<.001) or underwent mechanical ventilation during admission (84% vs 91%, P<.001). Patients with an elevated CRP had higher Body Mass Indexes (BMI 27 vs 26, P=.03) and were admitted with higher lactates (6.4 vs 5.7 mmol/L, P=.01) and a lower EF (P=.05), while more underwent mechanical ventilation during admission (92% vs 82%, P<.001). Elevated WBC among patients alive at day 3 was associated with a significantly higher 30-day mortality rate of 43% vs 30%, Plogrank<.001. Patients with an elevated CRP had a mortality rate of 42% vs 29%, Plogrank<.001. (fig. 1, 2) In a multivariable model for each biomarker, adjusting for factors associated with mortality in AMICS, including age, sex, diabetes, stroke, out-of-hospital cardiac arrest, arterial lactate, LVEF and mechanical ventilation, an elevated inflammatory response remained significantly associated with mortality. (HR(WBC↑) = 1.63 [1.29;2.06], P<.001. HR(CRP↑) = 1.51 [1.21;1.90], P<.001). Conclusions: Leucocyte and CRP response at day 3 of admission are associated with increased mortality in AMICS.